PENYELESAIAN PERKARA WANPRESTASI DALAM ARISAN BERBASIS ONLINE - Brandon David; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2023)
In essence, Indonesia is a state based on law as stated in the Constitution of the Republic of Indonesia Article 1 paragraph 3, so that every community activity is regulated by using law as a tool to carry out order, justice, security and development. One form of guarantee provided by law in its products is the legal relationship between legal subjects and other legal subjects in the economic field which cannot be separated from everyday human activities with the existence of arrangements regarding agreements. One that relates to agreements is online-based arisan which is based on written or oral agreements, thus providing protection to legal subjects to avoid unwanted things such as not having good faith in carrying out online arisan activities, especially those that can be a default form. Therefore the researcher uses a type of normative research method with a statutory approach. The results of this study are that the legal consequences arising from non-payment of online arisan funds can cause losses and are included in the category of default in the agreement so that they are required to compensate for losses and the conclusion in this study is that repayment can be carried out by means of litigation and non-litigation.